Paradogma of information or Paradigm of investigation, understanding and knowledge? - Viteri Briones, Telmo (Revista Universidad de Guayaquil, 2010)
This article externalized a cavilling about the Academy in the construction of a new teaching-learning paradigm: complex, socio-critical, holistic, of competency, strategic, multi-interdisciplinary, ecological and democratic, with an axis of research guideline in the curriculum practice and in scientific studies, technological, systematically adjusted with all educational levels in the country, the State Planning authorities and their partner requirements productive labor, cultural, historical, in the framework of the Knowledge Society and the report of the national market, regional and international.